2018
DOI: 10.1039/c7cs00914c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired construction of multi-enzyme catalytic systems

Abstract: Enzyme catalysis, as a green, efficient process, displays exceptional functionality, adaptivity and sustainability. Multi-enzyme catalysis, which can accomplish the tandem synthesis of valuable materials/chemicals from renewable feedstocks, establishes a bridge between single-enzyme catalysis and whole-cell catalysis. Multi-enzyme catalysis occupies a unique and indispensable position in the realm of biological reactions for energy and environmental applications. Two complementary strategies, i.e., compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 47 publications
2
107
1
Order By: Relevance
“…The majority of experimental investigations on hybrid lipid-copolymer vesicle are of hybrid GUVs for the convenience in characterization, since fluorescent-labeled microsized domains can be observed directly under fluorescent microscopy. [83,84,[87][88][89] In comparison, studies on hybrid LUVs are inadequate owing to the difficulty in characterizing nanosized and even smaller domains, typically techniques such as small-angle neutron scattering (SANS), time-resolved Förster resonance energy transfer (TR-FRET) and cryo-transmission electron microscopy (Cryo-TEM) are employed. [179,180] From systematic experimental studies, it was found that the difference in molecular weight/structure, the chemical compatibility between hydrophobic segments, and the molar fraction of lipids and copolymers in hybrid vesicles could be important for thermodynamic considerations.…”
Section: Hybrid Vesicles Asymmetric Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of experimental investigations on hybrid lipid-copolymer vesicle are of hybrid GUVs for the convenience in characterization, since fluorescent-labeled microsized domains can be observed directly under fluorescent microscopy. [83,84,[87][88][89] In comparison, studies on hybrid LUVs are inadequate owing to the difficulty in characterizing nanosized and even smaller domains, typically techniques such as small-angle neutron scattering (SANS), time-resolved Förster resonance energy transfer (TR-FRET) and cryo-transmission electron microscopy (Cryo-TEM) are employed. [179,180] From systematic experimental studies, it was found that the difference in molecular weight/structure, the chemical compatibility between hydrophobic segments, and the molar fraction of lipids and copolymers in hybrid vesicles could be important for thermodynamic considerations.…”
Section: Hybrid Vesicles Asymmetric Vesiclesmentioning
confidence: 99%
“…For a prosperous and interdisciplinary field like synthetic cells, there are reviews summarizing from specific aspects, for instance, tailoring appearance of synthetic cells, [2,[70][71][72] elucidating specific functions of synthetic cell modules, [2,71,73] which include adhesion, [58] growth, [57] energy regeneration/conversion, [4,[59][60][61] gene circuits, [56,74] and cellular interactions, [75][76][77] exclusively focusing on applications of synthetic compartments such as delivery carriers [10,18,[78][79][80][81][82][83][84][85][86][22][23][24][25]42,47,48,55] and micro-/nanoreactors. [3,5,39,[87][88][89] However, there are no adequate state-of-art reviews with multidisciplinary perspective summarizing from the soft matter fundamentals to biomedical applications of synthetic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, this question is raised by synthetic biology e↵orts that use various scaffolding strategies to construct e cient multi-enzyme complexes [48][49][50], inspired by natural complexes consisting of multiple enzymes in intricate arrangements [51]. Here, we explore this question from a theoretical perspective, starting with the idealized scenario of spherical catalysts that can be freely arranged into complexes with any geometry: how should the catalysts be arranged to globally maximize the pathway flux j P ?…”
Section: Geometries Of Optimal Complexesmentioning
confidence: 99%
“…In biological systems, enzyme or protein analytical sensing system could combine with the specific recognition site or binding affinity as a sensing system to design the analytical platform [64] Using the substrate DNA as an efficient template for determining nuclease or protein activity has many advantages, such as simplicity, rapidness, sensitivity, and userfriendly. [65] An assay has been designed to detect the 3'-5' exonuclease activity by using dsDNA-templated Cu-NPs.…”
Section: Bioassay For Enzyme Protein and Exosomes Analysismentioning
confidence: 99%